An Analysis Of Financial Statements Based On Isak 35 At Al-Ikhlas Foundation, Bengkulu City - Sumarti, Yeliana Agus; Sumarlan, Ahmad (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2023)
Non-profit organizations in carrying out their programs use resources that come from the community, so from the accountability point of view, their financial reports must be open and accountable to the public. The purpose of this study is to analyze the application of ISAK No.35 to the Al-ikhlas foundation in Bengkulu City.This research technique is a qualitative type. Data collection techniques used are interviews and documentation. The method of data analysis was carried out in three stages, namely, data reduction, data presentation and drawing conclusions.The results of this study explain that the Al-Ikhlas Foundation, Bengkulu City. Overall, the presentation of the financial statements of the Al-Ikhlas Foundation is in accordance with the Interpretation of Financial Accounting Standards No. 35 concerning Presentation of Financial Statements of Non-Profit Oriented Entities. However, some items have not followed the rules in the interpretation of financial accounting standards (ISAK) 35.